The Exact Nonrelativistic Energy Eigenvalues for Modified Inversely Quadratic Yukawa Potential Plus Mie-type Potential - Abdelmadjid Maireche (Журнал нано- та електронної фізики)
The modified theories of noncommutative quantum mechanics have engrossed much attention in the last decade, especially its application to the fundamental three equations: Schrödinger, Klein-Gordon and Dirac equations. In this contextual exploration, we further investigate for modified quadratic Yukawa potential plus Mie-type potential (MIQYM) in the framework of modified nonrelativistic Schrödinger equation (MSE) using generalization of Bopp’s shift method and standard perturbation theory instead of using directly the generalized Moyal-Weyl product method, we obtained modified energy eigenvalues and corresponding modified anisotropic Hamiltonian operator in both three dimensional noncommutative space and phase (NC-3D: RSP) symmetries.